Analisis Unjuk Kerja Pompa P-8340A Pada Motor Listrik Dan Motor Diesel Di Tangki T-8320A/B - Norhidayah, Siti; Kusmianto, Herdi; Hurung Anoi, Yano; Muliawan, Arief (Journal of Applied Mechanical Engineering and Renewable Energy, 2025)
This research aims to analyze the performance of the pump P-8340A operated by an electric motor and a diesel motor in the tank T-8320A/B. Apart from focusing on the performance of the two types of motors as pump drivers, this study also evaluates the time to fill the fire fightine water tank and the factors that influence the operational efficiency of the pump.The research methods used include taking field data at the operating location, analyzing flow capacity, pressure head and speed head, as well as calculating pump power and efficiency. The analysis results show that pumps with electric motors have a longer charging time compared to diesel motors, namely 38 hours for electric motors and 29 hours for diesel motors, with flow capacities of 239.68 m³/h and 310.54 m³/h respectively.From this research it was also identified that the total head losses in the pump were influenced by friction factors in the piping system and the characteristics of the fluid being transferred. The conclusion of this research is that although electric motors are more efficient in energy consumption, diesel motors are still superior in capacity and speed in operating the P-8340A pump. Recommendations for future operations include closer monitoring of the piping system and considering modifications to the drive system according to operational needs.